HUBUNGAN TANGGAPAN DAN SIKAP WARGA KOTA MADIUN TERHADAP MEMBAYAR ZAKAT/ JIZYAH SEBAGAI SUMBER APBN/APBD - Siti Muhayati; Diana Ariswanti Triningtyas; Juli Muwarni (Counsellia: Jurnal Bimbingan dan Konseling, 2015)
Between Budget and Budget State Local Income in equality especially lower budget fromthe budget, and 50%-60% Budget spent for paying employees the reasons is the lack ofparticipation of citizens to fund the management of the state by paying the zakat (Muslim)jizyah (non-Muslim). The purpose of this study was to determine the response and attitude ofthe towns people Madiun to pay Zakat/jizyah as a source of state budget/budget. This researchwas conducted in Madiun by taking a sample of three villages of nine districts. The method isquantitative with ex-post facto design, collection document and questionnaire data and dataproduct moment correlation analysis (T test). Results zero hypothesisis accepted becauset0(0.059) is smaller than tt(1.96) level significansi 5% or 1% (2.59), this shows that a person'sresponse to the zakat/jizyah as a source of state budget/budgetis proportional. Or no differencein the attitude of paying zakat/jizyah, both of whichare clear about the function of zakat, isbeing, or less. Respondents who understand the positive response is proportional to attitudes,respondents were then negative response is proportional to the negative attitude; respondentswere not sure what it is a very negative response is proportional to the extremely negativeattitude or do not pay zakat.